2022
DOI: 10.12928/telkomnika.v20i2.23158
|View full text |Cite
|
Sign up to set email alerts
|

Design of resonator cavity for liquid material characterization

Abstract: Dielectric characterization is very essential before the material can be utilized in designing microwave networks. Circular cylindrical resonators have been widely used for material characterization, but it is not a preferable design during the measurement of liquid samples as the sample placement requires repetitive process of opening and closing the lid of the cavity. This repetition procedure easily affects the accuracy of measurement and may lead to a measurement error. In this study, a rapid and less meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The permittivity measurement can be performed using the free-space, waveguide [29][30][31], or resonant [32][33][34][35] techniques. In this study, the permittivity was measured using the waveguide technique in the microwave region [29,30], with the measurement taking place in the G-band, which covers the frequency ranges of 3.95 to 5.85 GHz.…”
Section: Permittivity Test Of Cellulose Fibersmentioning
confidence: 99%
“…The permittivity measurement can be performed using the free-space, waveguide [29][30][31], or resonant [32][33][34][35] techniques. In this study, the permittivity was measured using the waveguide technique in the microwave region [29,30], with the measurement taking place in the G-band, which covers the frequency ranges of 3.95 to 5.85 GHz.…”
Section: Permittivity Test Of Cellulose Fibersmentioning
confidence: 99%
“…Permittivity measurement could be done using either free-space, waveguide [34,35], or resonant techniques [36][37][38][39]. In this work, wide-band measurement, i.e., waveguide technique, is preferred in order to provide dielectric value for wide applications.…”
Section: Permittivity Testmentioning
confidence: 99%
“…Another study has discussed antenna material [19] followed by [20] that could be used in wireless applications based on material permittivity, while trough gathering more electrical properties could achieve notable power radiation. Nevertheless, in [21] the liquid material characterization had been explored via dielectric characterization with unadvisable measurement of liquid samples due to the repetitive process of opening and closing the lid of the cavity that could lead to errors in the measurement process. Whereas the dielectric dense patch antenna was proposed in [22] to study Zamzam and distilled water at 5 GHz applications, and the significant result demonstrated a return loss between 4.41-5.52 GHz that reaches up to -10 dB, hence the strongest aspects of the study is considering the water composition which is could play a vital role in terms of propagation performance.…”
Section: Introductionmentioning
confidence: 99%